Atypical shape bias and categorization in autism: Evidence from children and computational simulations. Issue 2 (23rd July 2019) - Tovar, Ángel Eugenio; Rodríguez‐Granados, Angélica; Arias‐Trejo, Natalia
Abstract: The shape bias, a preference for mapping new word labels onto the shape rather than the color or texture of referents, has been postulated as a word‐learning mechanism. Previous research has shown deficits in the shape bias in children with autism even though they acquire sizeable lexicons. While previous explanations have suggested the atypical use of color for label extension in individuals with autism, we hypothesize an atypical mapping of novel labels to novel objects, regardless of the physical properties of the objects. In Experiment 1, we demonstrate this phenomenon in some individuals with autism, but the novelty of objects only partially explains their lack of shape bias. In a second experiment, we present a computational model that provides a developmental account of the shape bias in typically developing children and in those with autism. This model is based on theories of neurological dysfunctions in autism, and it integrates theoretical and empirical findings in the literature of categorization, word learning, and the shape bias. The model replicates the pattern of results of our first experiment and shows how individuals with autism are more likely to categorize experimental objects together on the basis of their novelty. It also provides insights into possible mechanisms by which children with autism learn new words, and why their word referents may be idiosyncratic. Our model highlights a developmental approach to autism that emphasizes deficient representations of categories underlying an impaired shape bias. Abstract : On average, children with autism do not show a shape bias when they extend new names to objects. Here we analyzed the shape bias in typically developing children and in children with autism, and we put forward a computational model that shows how the development of the shape bias requires preserved categorization abilities. The lack of the shape bias in autism may be strongly related to difficulties in basic categorization processes.